Use of the volume profile in making investment decisions on the stock market - Jóźwicki, Rafał; Trippner, Paweł (Journal of Finance and Financial Law, 2025)
The purpose of the article. In order to effectively multiply money on the capital market, it is necessary to use effective analytical methods to select the right financial instruments for an investment portfolio. This article focuses on the issue of the possibility to use the so-called volume profile to make investment decisions, which in its essence differs from classic indicators using turnover. In the article, the authors hypothesize that the volume profile makes it possible to identify the turning points of a listed instrument and thus can be an effective means for making investment decisions. On the basis of the assumptions made and in the light of the calculations performed, the research hypothesis presented in the introduction of the paper was positively verified. This indicates that the volume profile can be an important decision-making tool for investors and can thus be usefully applied in investment decision-making. Methodology. Overall, this study focuses on determining the reaction of the WIG20 index in relation to the volume profile of the session immediately preceding the day under analysis. The study used the WIG20 index from January to June 2024. Results of the research. According to the conducted analyses and calculations, a noticeable reaction of the WIG20 index value to the POC of the preceding session took place in approximately 90% of cases, which clearly indicates that this level determined during a given trading session is of significant importance for the course of quotations in the following day’s session.